Đặc điểm trầm tích Đệ tam trũng Đồng Giao - Huyên, Nguyễn Xuân; Pha, Phan Đông; Sơn, Trần Thanh; Hoài, Vũ Thị Thu (Vietnam Journal of Earth Sciences, 2009)
Characteristics of Tertiary sediments from the Dong Giao depression ...